Dyadic Death Series from An Autopsy Center: Femicide Suicides Cases - Balcı, Yasemin; Ekinci, Ecesu; Anolay, Nurettin Nezih; Çallak, Füsun (The Bulletin of Legal Medicine, 2023)
Objective: Dyadic death is a term generally used to describe cases in which the murderer committed suicide, usually after a murder, or cases where two people committed suicide together. In the cases that underwent autopsy in Muğla, between 2013 and 2021, the crime scene and dead examination reports were retrospectively analyzed, and those with dyadic deaths were evaluated and these cases were discussed. We believe that creating a database where dyadic deaths are recorded across the country, will shed light on understanding the dynamics of dyadic deaths. Methods: The crime scene analysis and dead examination reports of autopsies carried out between 2013-2021 in Muğla Forensic Medicine Branch Office were analyzed retrospectively.Results: In our case series, all 11 bilateral deaths were femicide-suicide and 9 of them used firearms for murder. In one of the cases, femicide occurred with a penetrating tool, and in the other case, it was caused by blunt head trauma.Conclusion: There is a partner relationship in all of the murders. Except for one case, all of those killed were women and all were spouses/ partners or ex-partners. These data in our case series show that dyadic deaths are an indicator of the violence against women in our country.
Keywords: İkili ölüm; Cinayet-İntihar; İntihar-İntihar; Otopsi